Efeito de diferentes rotas de processamento nas propriedades de armazenagem de hidrogênio da liga Mg – 8% p. Fe - Neves, André Martins (Universidade Federal de São Carlos, 2018)
Interested in developing new, and less dependent on non-renewable energy sources, researchers have been looking for different alternatives for energy systems in the recent years. The “Hydrogen Economy” is an alternative proposed which includes using hydrogen as an energy carrier. However, finding and developing suitable materials still a technological challenge. One method of storing hydrogen is through the use of metal hydrides, for which the Mg/MgH2 system is the most studied to this date. In order to improve its properties as a hydrogen carrier, many additives and processing routes were proposed and studied. The present work aims to investigate the effect of Fe addition and the influence of mechanical processing of melt-spun ribbons. As comparison, high pressure torsion discs were also produced with the same composition. HEBM was performed using pure powders from Mg and Fe (8% wt.) to obtain the mixture that underwent melt-spinning and was subsequently submitted to cold rolling. The hydrogenation kinetic behaviour of the ribbons and HPT samples was measured in a Sieverts-type apparatus. The (micro)structural aspects of the samples were investigated with XRD, SEM and TEM and the thermal properties of the absorbed samples were assessed by using DSC with TG and QMS coupled analysis. TEM imaging shows that a bi-modal distribution of Fe particles, ranging around 10-20 nm and 100-200 nm, was achieved in the ribbons. The results suggest that, in metallic ribbons and with the used composition, Fe does not have by itself a big effect in absorption kinetics, but does influence desorption. Furthermore, different processing routes give rise to different properties, but, within the studied scope, sample dimensions and cracks were the most important features after the first cycle for kinetic behaviour
The effect of different processing routes on the hydrogen storage properties of Mg – 8% wt. Fe alloy
Keywords: Materiais para absorção de hidrogênio; Sistema Mg-Fe; Processamento termo-mecânico de fitas metálicas; Hydrogen absorption materials; Mg-Fe system; Mechanical processing of melt-spun ribbons; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA